REMOVAL OF ORGANIC MATERIAL IN FREE WATER SURFACE GRAVEL BED FILTERS - Mayo, Aloyce W.; Ogombe, Hesborne S. (Tanzania Journal of Engineering and Technology, 2018)
The removal of organic material in free surface gravel bed filters was investigated and modelled. Two pilot wetland units of 7.5m x 1.5m x 0.7m were constructed adjacent to the University of Dar es Salaam waste stabilization ponds to receive maximum organic and hydraulic loading rates of less than 185 kg/ha/d and 110 l/m 2 /d, respectively. These units received wastewater of domestic characteristics from primary stabilization pond. The entire depth of 0.7 m of the wetland units were packed with gravel of size 8 25 mm and porosity of 35%. Samples were collected from the influent and effluent of wetland units and were tested for chemical oxygen demand (COD), temperature, dissolved oxygen, pH and other parameters useful for testing of the model. A semi-empirical model representing the major processes taking place in the wetland units was developed by incorporating suspended biomass, biofilm biomass, and sedimentation and filtration components. The model was optimized using computer program. The model was successfully developed and showed that biofilm of gravel media contributed significantly to COD removal in wetlands.